2020
DOI: 10.21203/rs.3.rs-68814/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Analysis of COVID-19 Clusters in India-Two Case Studies on Nizamuddin and Dharavi.

Abstract: Background- With the COVID-19 pandemic wreaking havoc across nations, several research projects are being carried out to study the propagation of the virus. In this study we have made an endeavour to analyse the spread of COVID-19 in the districts of India. Methods- Some districts in India have been much more a ected than the others. A cluster analysis of the worst a ected districts in India provide insight about the similarities between them. The e ects of public health interventions in flattening the curve i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
(6 reference statements)
0
8
0
1
Order By: Relevance
“…The NPIs should also reduce death by about 95%; SIR model was adopted for the simulations [53]. The other studies, reported in the Table 7, which involve lockdown in their analysis exhibit similar conclusions in terms of infection and death reduction after or while applying lockdown measures, based on statistics or simulations [1,18,57,69].…”
Section: Benchmark Studymentioning
confidence: 77%
See 3 more Smart Citations
“…The NPIs should also reduce death by about 95%; SIR model was adopted for the simulations [53]. The other studies, reported in the Table 7, which involve lockdown in their analysis exhibit similar conclusions in terms of infection and death reduction after or while applying lockdown measures, based on statistics or simulations [1,18,57,69].…”
Section: Benchmark Studymentioning
confidence: 77%
“…According to the analysis of the references [ 1 , 51 – 55 , 57 , 69 ], it was remarkable that the application of lockdown policies enhanced the slow-down of the spread of the pandemic in space and time. For instance, based on real-time statistics in Libanon, Kharroubi et Saleh [ 52 ] demonstrated the success of the lockdown measures on the containment of the disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tal fato pode ser explicado pelo risco aumentado de contaminação, causado por uma maior exposição provocada pela falta de reservas financeiras da população, que dificulta na adesão de medidas preventivas não farmacológicas, como isolamento social, uso de máscaras e higienização das mãos e, também, devido ao acesso limitado aos serviços de saúde (SANTOS et al, 2022). Alguns exemplos, seriam as comunidades carentes na Índia (SENGUPTA et al, 2021), e no Quênia (KIM et al, 2022).…”
Section: Vacinação De Populações Vulneráveisunclassified